Perbandingan Metode Isolasi Phosvitin dari Kuning Telur Ayam Buras untuk Karakterisasi Aktivitas Bioaktif - Andayani, I Gusti Ayu Sri; Iswaini, Dedy; Depamede, Sulaiman N; Kisworo, Djoko; Bulkaini, Bulkaini; Sriasih, Made (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to compare phosvitin isolation procedures from chicken egg yolk based on purity level, time efficiency, and functional activity. The procedures compared include previously published methods and modified methods developed in this study. Phosvitin was isolated from 10 samples of native chicken eggs collected from farms in the Mataram area using a stratified random sampling approach. The isolation process involved several sequential steps: sedimentation, centrifugation, dialysis, and lyophilization. A comparative analysis of the two procedures was conducted based on protein profile characteristics using SDS-PAGE and Fourier Transform Infrared (FTIR) spectroscopy to identify phosphate group interactions and metal ion binding. SDS-PAGE results showed that both procedures yielded Î±-phosvitin (35 kDa) and Î²-phosvitin (45 kDa) protein bands. FTIR spectra confirmed that both phosvitin samples contained high levels of phosphate groups, indicating strong phosphorylation and good protein stability. From a chemical and biological standpoint, the modified procedure showed no qualitative differences compared to the previously established method. However, the modified protocol was approximately 30 minutes faster and did not require a pH adjustment step, making it a simpler and more time-efficient alternative for isolating phosvitin from egg yolk.